P70 FINGER-TOE PULSE WAVE VELOCITY (FTPWV) MEASURED BY POPMèTRE® DEVICE IN PATIENTS WITH ANKYLOSING SPONDYLITIS - Guillermo Alanis-Sánchez; Carlos Ramos-Becerra; Ernesto Cardona-Muñóz; Diego Castañeda-Zaragoza; David Cardona-Muller; Hakim Khettab; Stephen Laurent; Pierre Boutouyrie; Hasan Obeid; Magid Hallab; Valeria Diaz-Rizo (Artery Research, 2018)
Background: Ankylosing spondylitis (AS) is an inflammatory autoimmune disease. AS is a prototype form of spondyloarthropathies (SpA). The precise ethology of AS has not been fully understood. But Inflammation has a critical role in the pathogenesis of the disease. Extra skeletal organs may also be affected by this disease and is also associated with an increase of cardiovascular risk. The effect of large arteries appears by a stiffness that can be an element of disease monitoring. Objective: The objective of this study was to evaluate the finger-toe Pulse Wave Velocity (ftPWV) in patients with AS. Methods: Finger-toe pulse wave velocity (ft-PWV) was measured by pOpmetre® allowed to explore arterial stiffness. Results: Demographic and clinical characteristics are presented in Table 1. Twenty-two patients with AS and 24 controls were included in our study, subjects with AS exhibited greater pSBP (p < 0.001), pDBP (p < 0.001), pPP (p < 0.001) and MBP (p < .001) compared to controls. Moreover, in the AS group we observed a higher ftPWV with a mean difference of 1.63 (p < 0.006, 95% CI of .50 to 2.7). No significant difference was observed in pPP. Conclusions: Individuals with ankylosing spondylitis showed increased ftPWV, central and peripheral blood pressure, this contributes to explain the higher risk of cardiovascular disease in this pathology. pOpmètre® is a no operator depended, simple and practical device, highlighted an increase in arterial stiffness in patients with AS by measuring the ft-PWV. It could play a role in this disease monitoring and in prediction of cardiovascular complications.